EFEKTIFITAS PEMBERIAN SANKSI LABEL SECURITY CHECKED TERHADAP PELANGGAR PARKIR KENDARAAN RODA EMPAT DI BANDARA NGURAH RAI - I Gusti Agung Dodik Dharma Sukanata (Fakultas Hukum Universitas Dwijendra, 2019)
Abstract Parking is a state of stationary vehicle or not moving for a while and abandoned by the driver. Parking facilities at the airport are very important. Not only used by the workers in the airport but also used by passenggers and the peoples who drop them off or pick them up. When the airport is busy there are many parking violations, especially parked their vehicle not on the parking lot provided. The importance of applying proper sanctions is the main idea of this research so that solutions and suggestions for the smoothness of the traffic in Ngurah Rai Airport can be found. The formulation of the issues raised are: 1.How is the effectiveness of using the labels of â€œsecurity checkedâ€ to be a sanction against parking offenders? 2. What is the proper sanctions for parking violation at Ngurah Rai Airport?This research usedjuridical empirical legal research methodwith descriptive research type. The data source consisted of primary data and secondary data. Data collection technique that used in this research was interviews. Data analysis used in this research is qualitative analysis.The conclusion based on this research are: 1. The effectiveness of using the labels of â€œsecurity checkedâ€ to be a sanction against parking offenders especially the four-wheeled vehicles at Ngurah Rai Airport was not effective because until the research completed there are still many parking violations and thesesanction is not regulated in Indonesian regulation. 2. The proper sanctions for the violation of parkir ban signs orparking carelessly at Ngurah Rai Airport must be referred to the Law Number 22 Year 2009 on Road Traffic and Transportation. Keywords: Effectiveness of sanctions, Label security checked, Parking Offenders.